Copper isotope effect in serum of cancer patients. A pilot study. Issue 2 (23rd December 2014) - Télouk, Philippe; Puisieux, Alain; Fujii, Toshiyuki; Balter, Vincent; Bondanese, Victor P.; Morel, Anne-Pierre; Clapisson, Gilles; Lamboux, Aline; Albarede, Francis
Abstract : Lower 65 Cu/ 63 Cu ratios in the serum of colorectal and breast cancer patients relative to healthy individuals have potential diagnostic value. Abstract : The isotope effect describes mass-dependent variations of natural isotope abundances for a particular element. In this pilot study, we measured the 65 Cu/ 63 Cu ratios in the serums of 20 breast and 8 colorectal cancer patients, which correspond to, respectively, 90 and 49 samples taken at different times with molecular biomarker documentation. Copper isotope compositions were determined by multiple-collector inductively coupled plasma mass spectrometry (MC-ICP-MS). When compared with the literature data from a control group of 50 healthy blood donors, abundances of Cu isotopes predict mortality in the colorectal cancer group with a probability p = 0.018. For the breast cancer patients and the group of control women the probability goes down to p = 0.0006 and the AUC under the ROC curve is 0.75. Most patients considered in this preliminary study and with serum δ 65 Cu lower than the threshold value of −0.35‰ (per mil) did not survive. As a marker, a drop in δ 65 Cu precedes molecular biomarkers by several months. The observed decrease of δ 65 Cu in the serum of cancer patients is assigned to the extensive oxidative chelation of copper by cytosolic lactate. The potential of Cu isotope variability as a new diagnostic tool for breast and colorectal cancer seems strong. Shifts in Cu isotope compositions fingerprint cytosolic Cu chelation by lactate mono- and bidentates. This simple scheme provides a straightforward explanation for isotopically light Cu in the serum and isotopically heavy Cu in cancer cells: Cu + escaping chelation by lactate and excreted into the blood stream is isotopically light. Low δ 65 Cu values in serum therefore reveal the strength of lactate production by the Warburg effect.